Single-center outcome after ablation of atrial fibrillation using very high-power short duration pulmonary vein isolation. (19th May 2022) - Manninger, M; Rohrer, U; Eberl, AS; Pratl, B; Loibnegger, S; Andrecs, L; Zirlik, A; Scherr, D
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Catheter ablation of atrial fibrillation is (AF) an established second line therapy for patients with symptomatic paroxysmal (PAF) and persistent AF (persAF). Novel ablation catheters with integrated thermocouples allow fast application of radiofrequency lesions with powers up to 90W. We aimed to describe primary and secondary outcomes after very high-power short duration (vHPSD) ablation. Methods: 126 consecutive patients (78 PAF, 43 persAF, 5 longstanding persistent AF) underwent pulmonary vein isolation (PVI) using the QDOT Micro Catheter (Biosense Webster) with the ablation mode QMODE+ (90W, 4s, interlesion distance ≤4mm anterior, ≤6mm posterior). Results: Mean age was 62±9 years, 33% were female, median CHA2DS2-VASc Score was 2 (0, 7). Median follow up duration was 204 (14, 461) days. 30% of patients had additional ablation of typical right atrial flutter. Primary success rate to achieve pulmonary vein isolation was achieved in all patients, no catheter-related complications (e.g., charring, steam pop) occurred. First pass isolation of all 4 PVs was achieved in 48% of patients, re-ablations were necessary in the carina regions (right: 37% of cases, left: 29%) and ridge (14%). Median procedure for PVI only were 102 (45-210) minutes. Arrhythmia-free survival was 79, 6% (see Figure 1). Eight patients underwent re-do procedures during follow-up showing most commonly showing gaps in the right inferior PV (63%) and ridge (50%). Conclusion: Very high-power short duration ablation allows safe and quick pulmonary vein isolation. However, first pass isolation rate is low due to gaps in the carina regions. Arrhythmia-free survival is comparable to other pulmonary vein isolation techniques. Figure 1: Left panel: Sample image of a vHPSD-PVI, posterior view of the left atrium. Right panel: Single procedure arrhythmia-free survival after vHPSD-PVI.